Experiences with IL-1 blockade in systemic juvenile idiopathic arthritis: data from the German AID-registry - Lainka, Elke Maria; Baehr, Melanie; Raszka, Bernadette; Haas, Johannes-Peter; Hügle, Boris; Fischer, Nadine; Foell, Dirk; Hinze, Claas; Weissbarth-Riedel, Elisabeth; Kallinich, Tilmann; Horneff, Gerd; Windschall, Daniel; et al. (Pediatric rheumatology, 2021)
Systemic juvenile idiopathic arthritis (sJIA) is a complex disease with dysregulation of the innate immune system driven by cytokines. A major role is ascribed to interleukin-1β (IL-1β), supporting the autoinflammatory character of the disease and offering an effective blocking mechanism for treatment. Here we present clinical practice data from the German AID-registry for patients treated with IL-1 inhibition (IL-1i).